Previous ovarian surgery increases the risk of tubal factor infertility - Hue HJ; Kim SK; Choi JY; Suh DH; Kim KD; No JH; Lee JR; Jee BC; Kim YB; Jeon HW (Clinical and Experimental Obstetrics & Gynecology)
Aim: Previous ovarian surgery for endometriosis results in decreased ovarian reserve and poor response to treatment in women with infertility. However, the impact of previous overall ovarian surgery on the incidence of infertility is unclear. Therefore the authors investigated impact of previous ovarian surgery on infertility incidence. Materials and Methods: This is a case-control study using retrospectively collected data in women who received infertility treatment (cases) or delivered babies (controls) at a tertiary center between 2003 and 2012. Results: The frequency of previous ovarian surgery was similar in both groups (p > 0.05) but it was higher in women with tubal infertility than their matched controls (p < 0.05). Also, the frequency of previous reproductive organ surgery was higher in the case group and in women with tubal or unexplained infertility (p < 0.05). Conclusion: Previous ovarian surgery is not associated with entire infertility, but may increase tubal factor infertility through adhesion formation and damage to adjacent tubes.